An Investigation into the Efficacy of a Structured Teaching Program on Understanding Pubertal Changes and Menarche Among Adolescent Girls Enrolled at a Designated PU College in Gadag - Ramesh Kamalappanawar; Ashwini; Shruti Hoogar; Jyoti Angadi; Heeru Jadhav; Shivaraj Kumbar; Sanjiv Haralayya (International Journal of Women's Health Nursing And Practices, 2024)
Background of the Study:Adolescence pertains to the phase of physical and physiological maturation occurring between childhood and adulthood. The commencement of adolescence, often linked to the initiation of puberty, introduces significant shifts in hormone levels and various ensuing physical transformations. The onset of puberty is also connected to substantial changes in drives, motivations, psychology, and social interactions, which persist throughout the adolescent period. A growing body of neuroimaging research is dedicated to examining the structural and functional evolution of the brain during adolescence. Objectives of the Study: (1) To appraise the understanding of pubertal changes and menarche among adolescent girls both prior to and following a structured teaching program. (2) To assess the impact of a structured teaching program on enhancing knowledge about pubertal changes and menarche among adolescent girls. (3) To explore the correlation between post-test knowledge scores and specific demographic variables. Method: A quasi-experimental in which pre-test, and post-test design without the control group were adopted for the present study. The planned knowledge questionnaire was developed based on the expert’s suggestions. The structured knowledge questionnaire was used to collect the data. After receiving permission from the college students, samples were selected by using a simple random sampling technique. Results: In the pre-test majority of the respondents (students) had inadequate knowledge (36%), moderate knowledge (54%), and adequate knowledge regarding pubertal changes and menarches. After the structured teaching program, knowledge increased adequate knowledge (74%). The mean difference between the pre-test and post-test is 2.63 and SD is 5.07. The Chi-square value of demographic value reviews only age and education are significant associations. Religion, type of family, and source of information are not significant associations. Conclusion: Based on the result we conclude that a structured teaching programme is effective in enhancing the knowledge of the PU students regarding pubertal changes and menarche
Keywords: Adolescent girls; Knowledge Enhancement; Menarche; Pubertal Changes; structured teaching program